Implemantasi Model Pembelajaran Kooperatif Tipe Grup Investigasi (GI) pada Mata Pelajaran SKI Kelas X MA Al-Bairuny Sambong Dukuh Jombang - Lubab, Muhammad Ahlis Irbabul; Al Ghozali, M. Dzikrul Hakim (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
This final project stems from the problem of the ineffectiveness of cooperative learning Investigation Group in MA Al Bairuny Sambong dukuh because it is still monotonous with lecture model. The purpose of this research is to find out how to use and the problems of Investigation Group Cooperative Learning at MA Al Bairuny.This research uses descriptive qualitative research. Collection tool the data uses observation, interviews, documentation. The data analysis technique using triangulation through data presentation, data reduction, drawing conclusions.The results of the study show that the application of the Cooperative Learning Model is of type The Investigation Group at MA Al Bairuny, namely the teacher makes groups later given a problem or discussion (topic) related to certain chapters. Then The groups were asked to discuss (exchanging ideas) in order to achieve something maximum results from the material discussed. While the problem is absence of students in class learning and student passivity.